1984
DOI: 10.1007/bf00229195
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone (GnRH) neurons and pathways in the rat brain

Abstract: Gonadotropin-releasing hormone (GnRH) neurons and their pathways in the rat brain were localized by immunocytochemistry in 6- to 18-day-old female animals, by use of thick frozen or vibratome sections, and silver-gold intensification of the diaminobenzidine reaction product. GnRH-immunoreactive perikarya were observed in the following regions: olfactory bulb and tubercle, vertical and horizontal limbs of the diagonal band of Broca, medial septum, medial preoptic and suprachiasmatic areas, anterior and lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
106
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(115 citation statements)
references
References 59 publications
9
106
0
Order By: Relevance
“…In contrast, those found in the sheep (Lehman et al 1986), springbok (Robinson et al 1997) and rhesus monkey have been reported to have a more complex morphology. It should be noted that the number of bipolar neurones identified in the present study may have been underestimated; many of the apparently unipolar GnRH cells in the rat brain have been shown to be bipolar using silver -gold intensification of the immunocytochemical staining (Merchenthaler et al 1984). In the male Djungarian hamster, differential changes in the incidence of these morphological subtypes have been observed during sexual maturation (Yellon & Newman 1991).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, those found in the sheep (Lehman et al 1986), springbok (Robinson et al 1997) and rhesus monkey have been reported to have a more complex morphology. It should be noted that the number of bipolar neurones identified in the present study may have been underestimated; many of the apparently unipolar GnRH cells in the rat brain have been shown to be bipolar using silver -gold intensification of the immunocytochemical staining (Merchenthaler et al 1984). In the male Djungarian hamster, differential changes in the incidence of these morphological subtypes have been observed during sexual maturation (Yellon & Newman 1991).…”
Section: Discussionmentioning
confidence: 57%
“…The GnRH neurones in the Damaraland mole-rat are predominantly unipolar and bipolar, as found in many mammals including the rat (Witkin et al 1982, Merchenthaler et al 1984, white-footed mouse (Glass 1986), Syrian hamster (Jennes & Stumpf 1980) and mink (Ntoumi et al 1992). In contrast, those found in the sheep (Lehman et al 1986), springbok (Robinson et al 1997) and rhesus monkey have been reported to have a more complex morphology.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that GnRH neurons actually form an interconnected network. Synapses have been shown between GnRH neurons (40,41,128,146,213,240). In addition, in vitro studies (119) of GT1-7 cells, the immortalized mouse GnRH neuronal cell line, showed that these cells expressed the message and the protein for the GnRH-receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The major regulator of reproduction in mammals, gonadotropin-releasing hormone (GnRH), is produced by neuronal cells located in the preoptic area and adjacent sites in the rostral portion of the hypothalamus and secreted into the hypophyseal portal vessels at the median eminence (1,2). The secretion of GnRH occurs in an episodic manner due to the activity of a hypothalamic GnRH pulse generator (3).…”
mentioning
confidence: 99%